O kruczej opowieści w Ramćaritmanas raz jeszcze - Stasik, Danuta (Gajt Wydawnictwo 1991 s.c., 2018)
In the most prominent of the Hindi Rāmāyaṇas, the sixteenth-century Rāmcaritmānas by Tulsīdās (1532–1623), the word communicated by the poet adopted the metaphorical form of the waters of Lake Mānas. The whole structure of the poem serves to construct this metaphor–its seven books (kāṇḍ) are visualized as the seven stairs (sopān) of the embankments (ghāṭ) leading to the lake, while the embankments themselves are identified with four structural dialogues, throughwhich the story of Rāma’s deeds (rāmkathā) is conveyed. One of the four characters conducting one of these dialogues, one of the narrators of rāmkathā, is a mysterious crow named Bhuśuṇḍi, who tells his story to Garuḍa, the king of birds. This paper attempts to discuss the place of ‘Bhuśuṇḍi’s Rāmāyaṇa’ in the structure of the Rāmcaritmānas, its specific function of a rāmkathā metastory and offers its interpretation. The discussion refers to previous research focusing on the textual relationships between the Yogavāsiṣṭha Rāmāyaṇa, the Bhuśuṇḍi Rāmāyaṇa and the Rāmcaritmānas. The analysis of the role of Bhuśuṇḍi as one of the poem’s narrators is aimed at broadening our understanding of the meaning of the four-dialogue-based text structure. It corroborates that this very structure is a carefully designed comprehensive tool, catering for the different needs of Rāma’s believers and allowing them to reach the core of the story’s mystery. The poem’s composition appears to be thoughtful and homogeneous, thus not giving much support to the concept of separate stages of its composition.
Keywords: Bhuśuṇḍi; Bhuśuṇḍi Rāmāyaṇa; Lake Mānas; Rāmcaritmānas; rāmkathā; Tulsīdās